A prospective randomised comparative study of dynamic, static progressive and serial static proximal interphalangeal joint extension orthoses. (March 2022) - Glasgow, Celeste; Ballard, Emma
Introduction: Many different types of proximal interphalangeal (PIP) joint extension orthoses exist, yet evidence guiding orthosis choice is largely theoretical. The primary aim of this study was to evaluate the clinical effectiveness of three different PIP joint extension orthoses, over 4 weeks of treatment. Secondly, we aimed to explore the relationship between an abbreviated version of the Weeks test (WT) assessment of joint stiffness, and treatment outcome. Lastly, we wished to better understand participants' satisfaction with orthotic treatment. Methods: Using a randomised comparative study design, 61 participants were allocated to a serial static, dynamic or static progressive orthosis, 50 had follow-up data. Blinded assessment of function was completed before and after 4 weeks of orthotic intervention and a standardised therapy program. Participants were blinded to alternative groups. Results: Baseline active PIP extension ranged from 14° to 65°. The average improvement in active PIP extension was −9.1° (95% CI −11.0°, −7.1°). There were no statistically significant differences in outcome between the three orthoses groups. However, a trend was observed with greater improvement in active extension for those in the dynamic Capener (−11.5°) compared to the static progressive belly gutter (−7.3°) or serial cast (−8.7°) groups, with less total end range time required. The abbreviated WT was significantly associated with improvement in active extension ( p = 0.001). Participants reported a high degree of satisfaction with their orthosis regardless of type. Conclusions: No single orthosis demonstrated statistically greater effectiveness, although the dynamic Capener orthosis appeared more efficient. The abbreviated WT is associated with treatment outcome.